Emojis and their significations - Sriphech, Somkiat; Sirikaya, Sirichai (Siam Communication Review, 2025)
This research article aimed to know the significance of top using Emojis on an online platform by qualitative research method, documentary research, and analysis with 10 Emojis (😂🤣❤️🙏😭😍✨🔥😊🥰). The result found that Emojis are significant by icon index and symbol. Emojis can used in emotional for emotions and functional for bullet points or message decoration arbitrary by user in symbiosis form. However, the signification of emojis depends on the contexts of communication become the codes